Laboratory testing of the antimicrobial effects of kyphi on a variety of micro‑organisms - Alicia Maravelia; Elsa Faviou; Emmanuel Magiorkinis; Markos Filianos (Pražské Egyptologické Studie)
Kyphi was used as both incense and medicament during a very long period in ancient Egypt, as is attested in Papyrus Ebers and other sources. The present work is a continuation of recent papers and a book concerning the comparative study of the ancient Egyptian kyphi and the Orthodox Holy Chrism, with freshly confected kyphi containing all its 16 ingredients, at the premises of the Oenological Chemical Laboratory of the Agricultural University of Athens. Based on the recent results obtained from two independent Laboratories, this study attempts, in a third independent Laboratory, both to replicate a part of the previous experiments and to extend the scientific investigation, comparing the effectiveness of ancient Egyptian kyphi and pure smoke on other micro organisms. The possible antimicrobial effects of pure smoke and of kyphi smoke are investigated by performing fumigation experiments on bacterial and fungal cultures. Thus, the antifungal and antimicrobial activity of kyphi is studied by performing fumigation experiments to cultivations of Morga nella morganii W. ssp morganii [Gram (–) bacterium], Escherichia coli M. [Gram (–) bacterium], Staphylococcus hominis K.&S. ssp hominis [Gram (+) coccus], Staphylococcus epidermidis W.&W. [Gram (+) coccus], Klebsiella pneumoniæ S.&T. ssp pneumoniae [Gram (–) bacterium], and Candida albicans (R.) B. [Gram (+) fungus] in different conditions. The results show that the action of fumigation (pure smoke and kyphi) on selective and differential culture media has almost no effect on the growth of micro organisms. However, there is a clear direct effect of smoke (pure smoke and kyphi) on the micro organisms that appears stronger with kyphi in all dilutions (and mostly in 1/1000). The experimental data reinforce the evidence from previous studies that the impact of kyphi on yeasts is mostly greater than that on bacteria and cocci, with indeed notable results at the 1/1000 dilution. The addition of all components of kyphi did not negate its antimicrobial activity but enhanced it, mainly against Gram (–) bacteria and less against Gram (+) cocci. Thus, the antimicrobial action of kyphi should be considered collectively, together with all its ingredients.